Seasonal variation in sprouting capacity from intact rhizome systems of three perennial weeds. (5th July 2013) - Boström, U; Andersson, L; Forkman, J; Hakman, I; Liew, J; Magnuski, E
Summary: The three rhizomatous perennials Elytrigia repens, Equisetum arvense and Tussilago farfara are all problematic in Scandinavian agriculture, due to their low susceptibility to soil cultivation. While repeated soil tillage is a fundamental part of the integrated control of these species, it is highly energy consuming and inefficient during periods when little sprout regrowth occurs. Substituting cultivation with mowing will reduce the environmental impact and labour costs, but its efficiency will still depend on the capacity of plants to sprout. Therefore, we studied the seasonal pattern in emergence and rhizome biomass allocation from July to April in six populations for each of the species. Plants were grown outdoors in pots buried in soil and exhumed at regular intervals in a two‐year experiment. In all three species, biomass allocation to rhizomes continued until late in the autumn. Emergence was severely impaired in E. arvense and T. farfara in September–October, while in E. repens, there was no such reduction in the number of emerged shoots. However, in the latter species, the shoot/rhizome ratio decreased and remained low until the plants had been exposed to a period of low temperatures. The increase in shoot/rhizome ratio for E. repens coincided with the resumed capacity to emerge for E. arvense and T. farfara . These results imply that there is no need to repeat a defoliation of E. arvense and T. farfara, if carried out in September–October. However, removal of the aerial plant parts early in the autumn is important to interrupt the upload of storage compounds to the rhizome systems of all species.